If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 180 = -6(7x + 12) Reorder the terms: 180 = -6(12 + 7x) 180 = (12 * -6 + 7x * -6) 180 = (-72 + -42x) Solving 180 = -72 + -42x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '42x' to each side of the equation. 180 + 42x = -72 + -42x + 42x Combine like terms: -42x + 42x = 0 180 + 42x = -72 + 0 180 + 42x = -72 Add '-180' to each side of the equation. 180 + -180 + 42x = -72 + -180 Combine like terms: 180 + -180 = 0 0 + 42x = -72 + -180 42x = -72 + -180 Combine like terms: -72 + -180 = -252 42x = -252 Divide each side by '42'. x = -6 Simplifying x = -6
| 4x+48=40+8+4x | | -312=-6(-7x-18) | | 9x-1*4x= | | -4x-4(x-1)=-32-4 | | 12+2p=3(4-5p) | | 2b-4-6b-6= | | 2.4h+1=7 | | -10n+3(8+8n)=-6(n+4) | | 75=42-3x | | 2(x-2)+3x=-6-8 | | 16=.432h-10.44 | | 16=.432-10.44 | | -3(5n-4)+3n= | | 2x+10-4x-5= | | -2.2x-3.35=6.25+x | | 4L-3=25 | | 15x-20=-3x+16 | | 4+c= | | 4xc= | | (x+4)(x+3)=18 | | 3x+4x=10 | | 4-3x=3.5 | | 10(x+5)=3(x+33) | | 4-3x=-15 | | 3(x-5)=57-5x | | 1000+600+6x=750+400+9x | | 2x-8=96-11x | | 15-y=13 | | 6-6k-2k= | | 2*(x+3)=8 | | 0=x^2+4x-3 | | 2(3x+4)=3x+2[3(x-1)+2] |